Pengaruh Literasi dan Promosi terhadap Penggunaan Shopee Paylater (Studi Mahasiswa Pascasarjana IAIN Parepare) - Andi Muhammad Fawzy Ramadhan; St. Nurhayati; Damirah Damirah; Syahriyah Semaun; Andi Bahri S (Departement of Mathematics Education, 2024)
Shopee Paylater's current usage has increased drastically as a result of the post-pandemic transition of its majority millennial user transactions especially among college students whose majority is literacy and promotion as a factor of influence. The purpose of this research is to find out the influence of literacy and promotion on the use of Shopeepay paylater on postgraduate students of IAIN Parepare. Result Research is a field research (Field Research) which is quantitative with an associative approach to knowing the influence of literacy and promotion on the use of Shopeepay paylater in postgraduate students of IAIN Parepare. The data analysis techniques used are quantitative descriptive with an associative approach. Which aims to find out the relationship between two variables or more.Research results show that: (1) Literacy (X1) has a significant influence on the use of Shopeepay paylater, proven with a significance value of 0,000 > 0.05 and a regression coefficient of 0.724.(2) Promotion (X2) has a significant influence on the use of Shopeepay paylater, demonstrated with a significance value of 0,801 < 0,05 and a regression coefficient of 0,037. (3) Then literacy (X1) and promotion (X2) have simultaneously or jointly influenced the use of Shopeepay paylater, proving a F-count value of 25,736 > F-table is 3.11 with a sig. p= 0,000 < 0.05.